Konsep Pendidikan Anak di Era Digital Dalam Perspektif Al-Qur’an - Muin, M. Tamsil; Setyawan, Aris (STAI Asy-Syukriyyah, 2024)
The purpose of this study is to find the concept of children's education in the digital era from the perspective of the Qur'an. The study uses a qualitative method using library research with a maudhu'i approach. Based on the results of the study, it was found that based on the letter Al-Alaq verses 1 and 4, the concept of children's education in the digital era must be able to integrate Al-Qur'an literacy with technological media where the integration process is that the teacher prepares the material to be studied (dilarized) then packaged and visualized through technological media so that meaningful and real learning is created that makes students' characters have a deep understanding of Islam and the creation of good Islamic characters.